1970
DOI: 10.1017/s0025315400004987
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of the Major and Some Minor Elements in Marine Animals I. Echinoderms and Coelenterates

Abstract: Many metallic elements are concentrated by marine animals to levels far in excess of their concentrations in sea water itself. This concentration extends not only to those elements which are known to have biochemical functions, but also to others which have no established biological role (e.g. cadmium and lead). Little is known about the mechanisms by which trace elements are concentrated, or about the manner in which they are held in the tissues. As a preliminary to the investigation of concentration mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…2. Terrestrial biological data are from Shacklette (1980), Elias et al (1982), Price et al (1985), Sealy and Sillen (1988), Gilbert et al (1994), Burton et al (1999), Blum et al (2000), Poszwa et al (2000), Sponheimer et al (2005), Drouet and Herbauts (2008) and marine biological data are from Mauchline and Templeton (1966) Szabo (1967), Martin (1970), Riley and Segar (1970), Segar et al (1971), Martin and Knauer (1973), Patterson and Settle (1977), Sealy and Sillen (1988), Gilbert et al (1994), Zumholz et al (2006), Cunha et al (2008), and Love et al (2009); more information on references is given in Electronic Annex EA-1. spanned three and three and a half orders of magnitude, respectively.…”
Section: Ba/ca Datamentioning
confidence: 99%
“…2. Terrestrial biological data are from Shacklette (1980), Elias et al (1982), Price et al (1985), Sealy and Sillen (1988), Gilbert et al (1994), Burton et al (1999), Blum et al (2000), Poszwa et al (2000), Sponheimer et al (2005), Drouet and Herbauts (2008) and marine biological data are from Mauchline and Templeton (1966) Szabo (1967), Martin (1970), Riley and Segar (1970), Segar et al (1971), Martin and Knauer (1973), Patterson and Settle (1977), Sealy and Sillen (1988), Gilbert et al (1994), Zumholz et al (2006), Cunha et al (2008), and Love et al (2009); more information on references is given in Electronic Annex EA-1. spanned three and three and a half orders of magnitude, respectively.…”
Section: Ba/ca Datamentioning
confidence: 99%
“…equina seem to be high in relation to concentrations reported to occur in coelenterates from the Irish Sea (Riley & Segar, 1970) and the Solent region of the United Kingdom (Leatherland and Burton, 1974) . Cadmium in Actinia equina however, is somewhat similar to levels found in both of those studies .…”
Section: Actinia Equina Linnaeus 1767mentioning
confidence: 72%
“…Wright (1980) noted a similar occurrence in the amphipod Gammarus pulex and found that the carapace accumulation reached a plateau after 60 h of exposure, indicating a limit in the adsorptive capacity of the exoskeleton. Riley and Segar (1970) also found the less-calcified portions of the sea star Asterias rubens and the echinoid Echinus esculentus to be richer in trace metals than more calcified tissues.…”
Section: Discussionmentioning
confidence: 88%
“…Cadmium is one of the most toxic heavy metals and has no established biological role (Riley andSegar 1970, Wright 1977a). Because only 5% of anthropogenic cadmium is recycled (Nriagu 1980), there are chronic problems with cadmium in sedimentary environments of industrialized countries (Furness et al 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation